Mahram For Women Hajj Pilgrims: Analysis of ‘illat and Development of Mahram Meaning - Busyro, Busyro; Ismail, Ismail; Wadi, Fajrul; Tarihoran, Adlan Sanur; Rosman, Edi (Madania: Jurnal Kajian Keislaman, 2020)
Discussion of the obligations of mahram for women in carrying out the pilgrimage has been discussed since the period of classical scholars to modern age. In fact, for women the pilgrimage is a means of jihad for them. Various thoughts have been put forward by scholars to interpret the Hadith about mahram, starting from textual understanding, which still requires mahram, to the discovery of ‘illat. This last understanding leads to the conclusion that having mahram is no longer necessary because the security as ‘illat can be realized. It is in this connection that this paper aims to compromise between textual understanding and the study of ‘illat so that it can be a solution for women pilgrims. This study used a descriptive analytical method with ‘illat study approach. The results showed that security for women pilgrims can be realized by using the meaning of mahram in terms of language, namely people who are forbidden to marry each other, so that fellow women is also a mahram. Therefore, their departure together with other women can realize the demands of nash without leaving nash textually. Perbincangan kewajiban mahram bagi perempuan dalam melaksanakan perjalanan haji sudah dibicarakan sejak periode ulama klasik sampai kontemporer. Bahkan, bagi seorang perempuan ibadah haji merupakan sarana jihad bagi mereka. Berbagai pemikiran dikemukakan oleh ulama untuk memaknai hadis tentang mahram, mulai dari pemahaman tekstual, yang masih tetap mewajibkan bermahram, sampai kepada penemuan ‘illat. Pemahaman terakhir ini membawa kepada kesimpulan bahwa bermahram tidak diperlukan lagi karena keamanan sebagai ‘illat sudah dapat direalisasikan.  Dalam kaitan inilah tulisan ini bertujuan mengkompromikan antara pemahaman tekstual dengan kajian ‘illat agar bisa menjadi solusi bagi jamaah haji perempuan.  Penelitian ini menggunakan metode deskripstif analitis dengan pendekatan kajian ‘illat. Hasil penelitian menunjukkan bahwa keamanan bagi jamaah haji perempuan dapat terealisir dengan menggunakan makna mahram dari segi bahasa, yaitu orang-orang yang haram saling menikah, maka sesama perempuan juga termasuk mahram. Oleh karena itu kepergian mereka bersama-sama dengan perempuan lainnya sudah dapat merealisasikan tuntutan nash tanpa meninggalkan nash secara tekstual.